Terminal bud and flower bud removal in short-season cotton - Beltrão, Napoleão Esberard de Macêdo; Nóbrega, Laudomiro Baldoíno da; Vieira, Dirceu Justiniano; Azevêdo, Demóstenes Marcos Pedrosa de; Sousa, Roberto Pequeno de (Pesquisa Agropecuaria Brasileira, 2014)
With the objective of evaluating the isolated and combined effects of terminal bud removal and debudding in uplan cotton (Gossypium hirsutum L.r. latifolium Hutch.), cv. CNPA Precoce 1, a field experiment was conducted during the rainy season of 1986 and repeated in 1987 at Sousa, PB, Brazil. In 1986, in a nonfertilized soil it was verified that bud removal realized after fifty days of plant emergence, increased the earlyness in 6.7%, reduced plant height by 16.2%, but did not alter stem diameter and cotton yield. The flower bud removal during the first 28 days after budding start, reduced cotton yield by 23.7% and earlyness from 78.0 tu 29.6%. In 1987, with fertilized soil, the terminal bud removal did not reduce yield, earlyness, and stem diameter but reduced plant height by 31.9%. Flower bud removal reduced earlyness from 50.5 to 22.9% and did not reduce yield
Keywords: early cultivar; Gossypium hirsutum; earliness; fibre quality; interaction